2016
DOI: 10.1007/s00192-016-2963-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parity on ewe vaginal mechanical properties relative to the nonhuman primate and rodent

Abstract: Introduction and hypothesis Parity is the leading risk factor for the development of pelvic organ prolapse. To assess the impact of pregnancy and delivery on vaginal tissue, researchers commonly use nonhuman primate (NHP) and rodent models. The purpose of this study was to evaluate the ewe as an alternative model by investigating the impact of parity on the ewe vaginal mechanical properties and collagen structure. Methods Mechanical properties of 15 nulliparous and parous ewe vaginas were determined via unia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…It was not possible to use the Valsalva maneuver in ewes; it is therefore possible that the incidence of POP in ovine cohorts may have been higher. Only one study reported POP-Q in a small number of sheep (n = 15), but at post mortem-and consistent with our findings-there is greater anterior and posterior vaginal wall descent observed in the parous relative to nulliparous ewes [13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It was not possible to use the Valsalva maneuver in ewes; it is therefore possible that the incidence of POP in ovine cohorts may have been higher. Only one study reported POP-Q in a small number of sheep (n = 15), but at post mortem-and consistent with our findings-there is greater anterior and posterior vaginal wall descent observed in the parous relative to nulliparous ewes [13].…”
Section: Discussionsupporting
confidence: 89%
“…A shorter perineal body and larger GH was found in the multiparous ewes, which could be explained by vaginal birth damage, and in one study, a larger GH and PB were strongly associated with prolapse [13,20,21]. A large GH would make vaginal access easier while operating and may be a useful measure for selecting ewes for vaginal surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study also supports a recent report comparing the mechanical properties of ewe vagina in non-human primates and rodent models where parity had a negative impact on mechanical integrity38. Though further comparative studies between these species are warranted, the similarities already identified suggests that ewes can be used for further investigations.…”
Section: Discussionsupporting
confidence: 89%
“…However, some of the greatest remaining challenges stem from the ethical issues surrounding procurement of human tissues, in significant quantities, that span the average 35-year time gap between maternal birth injury and the onset of symptoms for POP [11, 12]. Thus, researchers have begun to implement cross-disciplinary techniques to help bridge the gap.…”
Section: Introductionmentioning
confidence: 99%